RELAÇÕES ECOLÓGICAS ENTRE A FAUNA ICTIOLÓGICA E A VEGETAÇÃO CILIAR DA REGIÃO LACUSTRE DO BAIXO PINDARÉ NA BAIXADA MARANHENSE E SUAS IMPLICAÇÕES NA SUSTENTABILIDADE DA PESCA REGIONAL - Araujo, Naíla Arraes de (2008)
The lacustrine area of Penalva, in the Baixada Maranhense region, is formed by the lakes Cajari, Capivari, Lontra and Formoso, which encompass a diversified ciliary vegetation. Those environments, subject to the influence of seasonal floods, provide a variety of habitats for shelter, reproduction and feeding of fish species. Some of the fish species, as they feed from fruits and seeds from ciliary plant species they help in the process of seed dispersion, contributing to the reproductive success of the plants. This research aimed at studying the relationship between the ichthyologic fauna of the lacustrine area of Penalva and the ciliary vegetation and its implications in the sustainability of the regional fishing. More specifically, to analyze the relationship among the different plant species and the reproductive period, feeding habits and shelter of the fish species, investigating which species are dependent on the ciliary vegetation and which species function as seed dispersers. The methodology included, in a first phase, interviews with fishermen (key informants), by using semi-structured questionnaires, to record the traditional knowledge on fish and vegetation. In a second phase, monthly collections of fish specimens from the lakes Cajari and Capivari were carried out in the period April, 2007 to June, 2008; following the collections, the specimens were taken to laboratory analyses. The results showed that fishermen possess a vast knowledge on the relationship between the ichthyofauna and the regional ciliary vegetation, making clear the dependence between fish and plants. In this study eleven fish species were identified as seed dispersers of eleven ciliary plant species. In the rainy season, when extensive vegetation areas are flooded, the biggest number of fish specimens was recorded with full stomachs, as well as the biggest number of males and females in the maturation phase, confirming the importance of the ciliary forests for the ichthyofauna. The ciliary forests of the lacustrine area of Penalva have been suffering along the years from deforestation and burning that also affect fishing and local man. The effects from vegetation suppression can be already felt with the decrease of the size and quantity of fish species and individuals, according to local people. It is clear, therefore, the relationship between the reduction of the ciliary vegetation and the signs of fishing decline in the region. If control measures and conservation actions are not taken, sustainability of regional fishing can be seriously compromised.